Effects of Search Success on Search Engine Re-Use - Hu, Victor; Stone, Maria; Pedersen, Jan; White, Ryen W. (20th ACM International Conference on Information and Knowledge Management (CIKM 2011), October 24-28, 2011, Glasgow, United Kingdom, 2011)
People’s experiences when interacting with online services affects their decisions on re-use. Users of Web search engines are primarily focused on obtaining relevant information pertaining to their query. Search engines that fail to satisfy users’ information needs may find their market share to be negatively affected. However, despite its importance to search providers, the relationship be-tween search success and search engine re-use is poorly under-stood. In this paper, we present a longitudinal log-based study with a large cohort of search engine users that quantifies the relationship between success and re-use of search engines. We use time series analysis to define two groups of users: stationary and non-stationary. We find that recent changes in satisfaction rate do correlate moderately with changes in rate of return for stationary users. For non-stationary users, we find that satisfaction and rate of return change together and in the same direction. We also find that some effects are stronger for a smaller player on the market than for a clear market leader, but both are affected. This is the first study to explore these issues in the context of Web search, and our findings have implications for search providers seeking to better understand their users and improving their experience.